Emergence and Prevalence of Persistent and Residual Speech Errors - Flipsen, Peter, Jr. (Seminars in Speech and Language, 2015)
This report reviews the existing literature on the emergence and prevalence of speech sound errors in older children and adults. Findings from several different sources suggest that 1 to 2% of the young adult population overall may present with these errors. Up to 75% of these errors may resolve on their own between the end of the developmental period (i.e., age 9 years) and the end of high school, though speech therapy services may still be justified to reduce any negative social consequences of these errors. At least two different sources of these errors are postulated. Residual speech errors (the more common of the two types) appear to arise as a leftovers from a much earlier speech delay and were originally omission or substitution errors but migrated closer to normal to become distortions. Persistent speech errors, on the other hand, appear to be distortions from an early age that reflect long-instantiated habits. Whether this distinction points to different responses to particular interventions, or whether either type is more or less likely to resolve spontaneously is not clear at this time.
Keywords: Etiology; prevalence; residual speech error; persistent speech error